The negro: his position and possibilities and suggestions on probable solution of question - Potter, Luther Eugene (My University, 1900)
Introduction: Not to his dark African home do we wish to call your full attention, to wild and desperate deeds, or carry you through the probably history of his origin and render you incapable of sustaining a wise thought for him; but we wish you to be able to think clearly and soberly of him who has come among us to sup at our board, and answer with feeble voice of fear and mingled joy, when the age calls him brother. We wish you to see as plainly as possible from our present day observations of tendencies, the whole aspect of possibilities for this unfortunate. Even the school-boy of ten, knows his history in its novel pictures, and drops a tear of pity only to be dried as age creeps over him, and by outside influences, gives to it a growth of distrust with only the rudiments of pity left; while the negro with his black coat absorbs the delicate rays of sunshine, and gives its energy in the bubbling spring of joy so deep and sparkling that only God himself can realize its depths. Could you look at him as you do at yourself, and realize in him the passions, dreads and desires as in you, could you bring back your childhood, and speak plainly to your conscience, since you have it trained to response, you could see and respect his feelings and desires. At one time all men seemed to be possessed with predominant selfish motives, and with a dread, almost hate, for what is below them; and at another, under the stimuli of moral teaching and mingled religion, soar away in song and prayer for the redemption and betterment of the poor in cities, or the negro in his supposed illiteracy, subject to harshness of Southern tyranny; while beneath their own roof creeps the rat that gnaws continually to destroy their happiness and they see it not.
Citation: Potter, Luther Eugene. The negro: his position and possibilities and suggestions on probable solution of question. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Negro; Sociology; Racial Issues; Theses